INTEGRITY ANALYSIS OF CORRODED PIPELINE CAUSED BY SULFATE REDUCING BACTERIA (SRB) CASE STUDY: OFFSHORE PIPELINE IN JAVA SEA - Afif Hidayat, Muhammad
16-inch oil pipeline near North Java Sea experienced metal loss caused by Sulfate Reducing Bacteria (SRB). The depth of corrosion had reached 80% in 2010 based on Inline Inspection (ILI), while pipeline is still operating more than 20 years. In 2021, two leaks occurred in KP 45.919 and KP 45.165 so the corrosion assessment carried out to determine corroded pipeline strength to guarantee pipeline integrity. The research was conducted to analyze pitting and local corrosion based on DNVGLRP- F101, API 579 part 6 assessment, and finite element method until pipeline would operate on August 2025. Besides that, the parametric study was conducted to determine the effect of corrosion dimension variables on resistance pressure and Remaining Strength Factor (RSF) as corroded pipeline strength parameters. Girth weld 29190 was analyzed using corrosion rate variation from 0.39 mm/year to 0.1 mm/year. The results showed that girth weld 29190 was rejected based on DNVGL-RP-F101 as single and interacting defect. Girth weld 29190 was rejected based on level 1 API 579, but accepted based on level 2 API 579. Finite element simulations showed that girth weld 29190 would be accepted until August 2058 for corrosion rate 0.1 mm/year, August 2031 for corrosion rate 0.21 mm/year, and January 2023 for corrosion rate 0.39 mm/year. The study parametric results based on finite element simulation showed that the depth of corrosion and the corrosion spacing below 101.6 mm to 127 mm reduced pipeline strength. Simulation result was close to resistance pressure and minimum space requirement for interacting defect based on DNVGL-RP-F101.